2019
DOI: 10.1371/journal.pone.0211109
|View full text |Cite
|
Sign up to set email alerts
|

A pricing model for group buying based on network effects

Abstract: Group buying (GB) is a popular business model in e-commerce. With the rise of online social media, the positive network effect of buying with others is more important than price discount for consumers to choose GB. However, the negative network effect of GB is also significant for some consumers. In this paper, we classify consumers into two segments considering both positive and negative network effects, and three possible sales strategies as well as their optimal decisions on price are presented. We find tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Qing et al (2018) [10] pointed out that the seller's reaction to online consumer negative comments (NCRs) has a significant effect on consumers' purchase intentions. Ni et al (2019) [11] found that price discounts and services in OCGB affect consumers' purchase intentions. Chen et al (2011) [12] studied the influence of trust on online group buying and determined that consumers have different intentions to participate in group-buying activities under different trust scenarios.…”
Section: Literature Review and Theoretical Foundationmentioning
confidence: 99%
“…Qing et al (2018) [10] pointed out that the seller's reaction to online consumer negative comments (NCRs) has a significant effect on consumers' purchase intentions. Ni et al (2019) [11] found that price discounts and services in OCGB affect consumers' purchase intentions. Chen et al (2011) [12] studied the influence of trust on online group buying and determined that consumers have different intentions to participate in group-buying activities under different trust scenarios.…”
Section: Literature Review and Theoretical Foundationmentioning
confidence: 99%
“…Some scholars have also studied group buying pricing strategies in specific situations. For example, Ni [12] considered both positive and negative network effects and proposed three possible sales strategies for group buying, individual buying, and hybrid buying, as well as their optimal decision on price. Wu et al [13] studied the method for restaurants to set group buying prices and the optimal promotion strategy for the platform, given the promotion level of group buying websites.…”
Section: Online Group Buying Pricing Strategiesmentioning
confidence: 99%